2020
DOI: 10.1177/1076029620929764
|View full text |Cite
|
Sign up to set email alerts
|

Local Thrombolysis in High-Risk Pulmonary Embolism—13 Years Single-Center Experience

Abstract: To evaluate the prognosis after local thrombolysis compared to systemic thrombolysis in high-risk pulmonary embolism. Observational study during 13 years which included 37 patients with high-risk pulmonary embolism treated with local thrombolysis and 36 patients with systemic thrombolysis (streptokinase, 250 000 UI/30 minutes followed by 100 000 UI/h). Cardiogenic shock has totally remitted in the group with local thrombolysis ( P = .002). The decrease in pressure gradient between right ventricle and right atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The standard CDT involves advancing the dedicated catheters into the culprit pulmonary artery with thrombus distribution for restoration of pulmonary blood flow by delivering thrombolytics ( 6 ). Multiple studies have demonstrated the advantage of immediate thrombus removal through percutaneous catheter-directed thrombectomy and aspiration by providing strong evidence of excellent safety, which may be credited to locally administered low-dose thrombolytics ( 7 , 8 ). The FLASH trial evaluated the effectiveness of percutaneous catheter-directed thrombectomy and aspiration for the treatment of intermediate to high-risk PE and showed it has a tendency toward superiority in immediate hemodynamic improvements and cardiac function recovery ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…The standard CDT involves advancing the dedicated catheters into the culprit pulmonary artery with thrombus distribution for restoration of pulmonary blood flow by delivering thrombolytics ( 6 ). Multiple studies have demonstrated the advantage of immediate thrombus removal through percutaneous catheter-directed thrombectomy and aspiration by providing strong evidence of excellent safety, which may be credited to locally administered low-dose thrombolytics ( 7 , 8 ). The FLASH trial evaluated the effectiveness of percutaneous catheter-directed thrombectomy and aspiration for the treatment of intermediate to high-risk PE and showed it has a tendency toward superiority in immediate hemodynamic improvements and cardiac function recovery ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fasullo et al compared hemodynamic effects of systemic thrombolysis against anticoagulation alone, with a finding that systemic thrombolysis was superior in RV/LV ratio improvement (1.4 ± 0.05➝1.12 ± 0.04) against anticoagulation alone in intermediate-risk patients (1.42 ± 0.04➝1.25 ± 0.04) [ 35 ]. Macovei et al reported improvement in sPAP between local (decrease from 51 to 15 mmHg and systemic thrombolysis groups in high-risk patients (decrease from 70 to 37 mmHg) [ 36 ]. Although our findings suggest a less dramatic decrease in sPAP with non-fibrinolytic based therapies, there still remained a statistically significant drop in sPAP.…”
Section: Discussionmentioning
confidence: 99%